2013
DOI: 10.1111/ijac.12117
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Properties of BioCeramic Coatings onto 3D Ti‐Mesh by DipCasting Method

Abstract: This study presents a dipcasting method that can deposit both porous and dense bioceramic coatings onto 3D Ti-mesh made from commercially pure Ti-mesh for surgical applications. First, a dense bioglass coating was deposited onto the 3D Ti-mesh, which is to seal off the Ti-mesh. Second, a microporous HA/bioglass coating was deposited on top of the dense bioglass coating, which is to promote bone regeneration into the 3D Ti-mesh. X-ray diffraction, field emission scanning electron microscopy, and energy dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…49−51 As shown in the magnified views in Figure 2f, g, the bioceramic scaffold was well-anchored onto the titanium mesh by the bioglass bonding layer without any interfacial cracking and delamination. The welding strength was 27 ± 0.7 MPa, within the reported bioglass bonding strength range of 20 to 30 MPa, 47 indicating that the entire hybrid cage could retain good structural integrity upon loading. EDS elemental mapping and line scanning results suggested that the reaction layer between the titanium mesh and bioglass bonding layer had a thickness of approximately 2 μm and contained the main elements of titanium, silicon, and oxygen (Figure 2g, h and Figure S1).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…49−51 As shown in the magnified views in Figure 2f, g, the bioceramic scaffold was well-anchored onto the titanium mesh by the bioglass bonding layer without any interfacial cracking and delamination. The welding strength was 27 ± 0.7 MPa, within the reported bioglass bonding strength range of 20 to 30 MPa, 47 indicating that the entire hybrid cage could retain good structural integrity upon loading. EDS elemental mapping and line scanning results suggested that the reaction layer between the titanium mesh and bioglass bonding layer had a thickness of approximately 2 μm and contained the main elements of titanium, silicon, and oxygen (Figure 2g, h and Figure S1).…”
Section: Resultssupporting
confidence: 63%
“…To manufacture such a titanium-bioceramic scaffold hybrid cage, we developed and optimized a unique multistep processing methodology of 3D slip deposition, 43,47 gel casting, freeze-drying, and cosintering 44 (Figure 2a). We combined HA and nWS in the bioceramic scaffold to achieve excellent osteoconductivity, osteoinductivity, and in vivo bone-forming ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some publications have presented the possibility to cover titanium‐based implants with bioactive materials, promoting a hybrid function, that is, combination of good mechanical properties and bioactive performance …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some publications have presented the possibility to cover titanium-based implants with bioactive materials, promoting a hybrid function, that is, combination of good mechanical properties and bioactive performance. 6,[10][11][12] Scaffolds are highly porous structures required in tissue engineering strategies, where tissue can regenerate by the attachment, growing and proliferation of new cells into a porous structure. 5,9 A scaffold should have the following characteristics: biocompatibility to enable cell attachment, differentiation and proliferation; osteoconduction, that is, stimulation of cell migration; biodegradability at a rate matching the rate of new tissue formation; mechanical strength during tissue reparation; and interconnected pore network for cell penetration, tissue ingrowth and vascularization.…”
Section: Introductionmentioning
confidence: 99%